2021
DOI: 10.1136/postgradmedj-2020-139382
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum haemorrhage and associated factors among mothers who gave birth in South Gondar Zone public health facilities, Ethiopia: a cross-sectional study

Abstract: BackgroundPostpartum haemorrhage is one of the direct and the leading causes of maternal morbidity and mortality. There are many risk factors of postpartum haemorrhage, which vary in different settings. Therefore, the purpose of this study was to assess postpartum haemorrhage and associated factors among mothers who gave birth in public health facilities.MethodsA cross-sectional study was employed from 17 November 2019 to 15 February 2020. The study participants were selected using a systematic sampling techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The results of this study showed that the likelihood of primary postpartum hemorrhage was high among women with APH, uterine atony, twin delivery, and prolonged labor. Almost all of these described factors agree with the findings of many other studies conducted both in developed and developing countries ( 2 , 6 , 10 19 , 32 , 35 , 36 , 39 , 40 ). Therefore, these similarities implied that those factors might be the common contributors to the occurrence of primary postpartum hemorrhage.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study showed that the likelihood of primary postpartum hemorrhage was high among women with APH, uterine atony, twin delivery, and prolonged labor. Almost all of these described factors agree with the findings of many other studies conducted both in developed and developing countries ( 2 , 6 , 10 19 , 32 , 35 , 36 , 39 , 40 ). Therefore, these similarities implied that those factors might be the common contributors to the occurrence of primary postpartum hemorrhage.…”
Section: Discussionsupporting
confidence: 90%
“…The current systematic review and meta-analysis included 21 primary studies with a total of 93,898 study participants. Of the total of 21 studies; 7 studies were conducted in Amhara region [11,[36][37][38][39][40][41], 6 studies in South nation nationality and people (SNNP) region [30,[42][43][44][45][46], 2 studies in Oromia region [10,47], 2 studies in Addis Ababa City administration [29,48], 1 study in Tigray region [49], 1 study in Dire Dawa City administration [50], 1 study in Harar region [51] and 1 study was conducted national-wide [52] (Table 1). Only 4 studies were conducted in rural area, the rest 17 were conducted in urban area.…”
Section: Characteristics Of the Included Articlesmentioning
confidence: 99%